2015
DOI: 10.1177/2513826x1500100308
|View full text |Cite
|
Sign up to set email alerts
|

Supernumerary Nostril: Report of a Rare Case and a Review of the Literature

Abstract: Supernumerary nostril is an extremely rare congenital entity that results from aberrant embryological development. A review of the literature reveals that only 33 cases of supernumerary nostril have been reported. They can be associated with other congenital anomalies. The accessory nostril may or may not communicate with the ipsilateral nasal cavity, probably depending on the degree of embryological progression of the anomaly. A case of supernumerary left nostril with no nasal cavity communication is presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…[20] This, "fissuring of the lateral nasal process" during development is the most accepted and cited theory by various authors. [19,20,21] This theory may explain the presence of supernumerary nostril occurring in isolation but fails to explain the anomalies associated which are present in significant (45%) percentage of patients and also presence of hydrocephalus as seen in our case. The presence of associated anomalies in supernumerary nostril cases may be due to early significant embryological interruption.…”
Section: Embryology Of Facial Development and Brain To Appreciate The...contrasting
confidence: 57%
“…[20] This, "fissuring of the lateral nasal process" during development is the most accepted and cited theory by various authors. [19,20,21] This theory may explain the presence of supernumerary nostril occurring in isolation but fails to explain the anomalies associated which are present in significant (45%) percentage of patients and also presence of hydrocephalus as seen in our case. The presence of associated anomalies in supernumerary nostril cases may be due to early significant embryological interruption.…”
Section: Embryology Of Facial Development and Brain To Appreciate The...contrasting
confidence: 57%
“…In cases of supernumerary nostril where the greater alar cartilage was under-developed, it was necessary to leave the nasal cavity retainer in place as aftercare [ 11 ]. Previous studies suggested for postoperative nasal retainer to be inserted for at least 2–3 months [ 12 , 15 ]. In our study nasal retainer was maintained for at least 4 months to prevent nostril contracture.…”
Section: Discussionmentioning
confidence: 99%
“…1 A review of the literature revealed that only 33 cases have been reported so far. 2 (1) Lindsay was the first to report such a case in the English literature in 1906. 3 (2) Tawse (1920) 4 described a patient with a unilateral supernumerary nostril, which communicated with the nasal cavity.…”
Section: Introductionmentioning
confidence: 99%